Soil Insect Diversity and Ecological Roles in Coffee (Coffea sp.) Agroforestry Systems of Purwodadi, Pasuruan - Nadiyah, Fatma Aulia; Refer Iqbal Tawakkal (Journal of Coffee and Sustainability, 2025)
This study aimed to analyze the diversity and ecological roles of soil insect communities in coffee (Coffea sp.) agroforestry systems in Purwodadi, Pasuruan, East Java. The research focused on identifying insect composition, abundance, and functional roles in supporting ecosystem processes. Sampling was conducted in September 2021 using pitfall traps arranged along transects within a one-hectare coffee agroforestry area characterized by diverse shade trees, including Swietenia mahagoni, Ficus benjamina, Mangifera indica, Ceiba pentandra, Leucaena leucocephala, Musa paradisiaca, Syzygium aromaticum, and Magnolia alba. Soil insects collected were identified to genus level, and ecological indices were calculated, including Shannon-Wiener diversity (H’), Simpson dominance (D), evenness (E), and Margalef richness (R). The results recorded 12 genera from 9 families comprising 204 individuals. Formicidae and Gryllidae were the most dominant families, with Brachyponera (73 individuals) and Gryllus (36 individuals) showing the highest abundance. Ecological indices revealed moderate diversity (H’ = 1.868), low dominance (D = 0.203), relatively high evenness (E = 0.752), and low species richness (R = 2.068). These findings highlight the crucial roles of soil insects as decomposers, herbivores, predators, and soil aerators, emphasizing their importance in sustaining nutrient cycles, regulating pest populations, and maintaining soil ecosystem stability in coffee agroforestry systems.